1995
DOI: 10.1021/bi00044a031
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of annexin II tetramer by tyrosine phosphorylation

Abstract: Annexin II tetramer (AIIt) is a Ca(2+)-dependent phospholipid-binding phosphoprotein. In cells either expressing transforming protein tyrosine kinases or treated with growth factors such as PDGF, AIIt has been shown to contain increased levels of phosphotyrosine. Therefore, we have examined the effects of the in vitro phosphorylation of AIIt by pp60c-src on several activities of the protein. AIIt was phosphorylated by pp60c-src to 0.91 +/- 0.07 mol of phosphate/mol of AIIt (mean +/- SD). The protein tyrosine p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
79
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 51 publications
(85 reference statements)
2
79
0
Order By: Relevance
“…However, precise mechanisms of AIIt-mediated fusion of plasma membrane and lamellar body in this exocytotic process are far from fully elucidated. The majority of the evidence for a role of AIIt in membrane fusion is based on model membrane (13,15,16,22). In this study we established a sensitive in vitro assay for the fusion of lamellar bodies with the plasma membrane using a fluorescent probe R18, and we demonstrated a critical role of AIIt and arachidonic acid in this process.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…However, precise mechanisms of AIIt-mediated fusion of plasma membrane and lamellar body in this exocytotic process are far from fully elucidated. The majority of the evidence for a role of AIIt in membrane fusion is based on model membrane (13,15,16,22). In this study we established a sensitive in vitro assay for the fusion of lamellar bodies with the plasma membrane using a fluorescent probe R18, and we demonstrated a critical role of AIIt and arachidonic acid in this process.…”
Section: Discussionmentioning
confidence: 85%
“…Serine or tyrosine residues near the N terminus of annexin II can be phosphorylated by protein kinase C and tyrosine kinase pp60 c-Src , respectively. In vitro phosphorylation of these sites reduces the ability of this protein to aggregate vesicles without affecting its membrane binding capacity (21,22). We have shown recently (23,24) that the modification of cysteine or tyrosine residues of annexin II by nitric oxide or peroxynitrite leads to the loss of its liposome aggregation activity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…SRC kinase can directly phosphorylate ANXA2 on Y23 [26,27], which may negatively modulate ANXA2 function and inhibit the ability of ANXA2 to bind F-actin [27]. However, another study showed that phosphorylation of ANXA2 Y23 is essential for ANXA2 function and its association with the endosome [19].…”
Section: Discussionmentioning
confidence: 99%
“…The ANXA2-S100A10 complex has a channel modulating effect on the cell surface which can affect the membrane interactions of lipids [29]. SRC kinase has been shown to phosphorlyate both ANXA2 [26,27] and S100A10 [30].…”
Section: Discussionmentioning
confidence: 99%